Upgrading bio‐oil model compounds phenol and furfural with in situ generated hydrogen. Issue 3 (6th January 2014) - Tan, Zhichao; Xu, Xingmin; Liu, Yonggang; Zhang, Changsen; Zhai, Yunpu; liu, Peng; Li, Yu; Zhang, Ruiqin
<x xml:space="preserve">Abstract</x> Bio‐oil produced from prolysis process of biomass cannot be directly used for transportation fuels, because of the poor quality. Catalytic hydrogenation is then used to upgrade bio‐oil to engine‐grade fuel. However, external H2 addition may not be cost effective to obtain high quality of oil. In this work, the feasibility of in situ hydrogen generation and hydrodeoxygenation is studied. Formic acid and acetic acid were selected as compounds for hydrogen generation by reforming reaction. Furfural and phenol were used as model bio‐oil compounds and were hydrogenated by in situ generated hydrogen from these acids using commercial Pd/C and Nickel based catalysts, RZ409. The reaction was performed in a batch‐scale reactor at 300°C for 3 h. The amount of H2 generation depended on the type of catalyst and substrate used. For example, 1 mol formic acid yielded 0.46 mol H2 (46% yield) and 0.46 mol CO2 with Pd/C, while it produced only 0.15 mol H2 and 0.15 mol CO2 with RZ490. The Furfural and phenol could be hydrogenrated and translated to different byproducts with in situ generated H2, with some byproducts identified. The results provide a clear rationale for utilization of in situ generated H2 for future bio‐oil upgrading to reduce external H2 usage. © 2014 American Institute of Chemical Engineers Environ Prog, 33: 751–755, 2014